BRAND EQUITY’S IMPACT ON PURCHASE DECISIONS MEDIATED BY PURCHASE INTENTION AT THILLAXSTUFF ON SHOPEE - Dameethia Angeline; Haris Maupa (International Journal of Application on Economics and Business, 2025)
The purpose of this research is to analyze the effects of brand awareness, brand loyalty, brand association, and perceived quality on consumers’ purchase decisions, with purchase intention serving as an intervening variable. The data were gathered through convenience sampling, involving 168 participants who had previously purchased hampers from THILLAXSTUFF via the Shopee platform. The analytical method utilized in this study was Partial Least Squares – Structural Equation Modeling (PLS-SEM). The findings reveal that: (1) brand awareness significantly influences purchase decisions; (2) brand loyalty significantly influences purchase decisions; (3) brand association significantly influences purchase decisions; (4) perceived quality does not have a significant effect on purchase decisions; (5) purchase intention does not significantly influence purchase decisions; (6) brand awareness significantly affects purchase intention; (7) brand loyalty significantly affects purchase intention; (8) the indirect effect of brand awareness on purchase decision via purchase intention is not significant; and (9) the indirect effect of brand loyalty on purchase decision via purchase intention is also not significant. These results indicate that brand awareness, loyalty, and association exert a direct influence on consumer purchasing behavior, while purchase intention does not significantly mediate those relationships in this particular context.